A Germylene/Borane Lewis Pair and the Remarkable C=O Bond Cleavage Reaction toward Isocyanate and Ketone Molecules. Issue 41 (19th August 2016) - Li, Jiancheng; Li, Bin; Liu, Rui; Jiang, Liuyin; Zhu, Hongping; Roesky, Herbert W.; Dutta, Sayan; Koley, Debasis; Liu, Weiping; Ye, Qingsong
Abstract: A germylene/borane Lewis pair (2 ) was prepared from a 1, 1‐carboboration of amidinato phenylethynylgermylene (1 ) by B(C6 F5 )3 . Compound2 reacted with i PrNCO and (4‐MeOC6 H4 )C(O)Me, respectively, with cleavage of the C=O double bond. In the first instance, O and i PrNC insert separately into the Ge−B bond to yield a GeBC2 O‐heterocycle (3 ) and a GeBC3 ‐heterocycle (4 ). In the second case (4‐MeOC6 H4 )(Me)C inserts into the Ge−N bond of2 while O is incorporated in the Ge−B bond to form a Ge‐centered spiroheterocycle (5 ). The reaction of2 with t BuNC to give6, which has almost the same structure as4, proved the formation of the isonitrile during transformation from2 and i PrNCO to3 and4 . The kinetic study of the reaction of2 and i PrNCO gave evidence of proceeding through a GeBC3 O‐heterocycle intermediate. In addition, a DFT study was performed to elucidate the reaction mechanism. Abstract : Give it a break : Germylene/borane Lewis pair1 reacts with i PrNCO and (4‐MeOC6 H4 )C(O)Me, respectively, with cleavage of the C=O double bond (see scheme). Fragments O and i PrNC insert separately into the Ge−B bond to yield2 and3, and O and (4‐MeOC6 H4 )(Me)C into the respective Ge−B and Ge−N bonds to form4 . The reaction of1 with an excess of i PrNCO leads to i PrNC, 2 (major) and3 (minor).